2013
DOI: 10.3390/toxins5020363
|View full text |Cite
|
Sign up to set email alerts
|

On The Role of Natural Killer Cells in Neurodegenerative Diseases

Abstract: Natural killer (NK) cells exert important immunoregulatory functions by releasing several inflammatory molecules, such as IFN-γ and members of chemokines, which include CCL3/MIP-1α and CCL4/MIP-1β. These cells also express heptahelical receptors, which are coupled to heterotrimeric G proteins that guide them into inflamed and injured tissues. NK cells have been shown to recognize and destroy transformed cells and virally-infected cells, but their roles in neurodegenerative diseases have not been examined in de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 79 publications
1
25
0
Order By: Relevance
“…These findings were in line with other observations showing that GA ameliorated clinical EAE scores, and that NK cells from these mice lysed both iDCs and mDCs [16]. These results indicated that one possible mechanism of GA inhibition may be to activate NK cells to lyse DCs (reviewed in [23]). Similarly, recent observations have shown that mitoxantrone, another drug used for treating MS, induces NK cell enrichment and maturation, which was associated with improved clinical response in secondary progressive MS [24].…”
Section: Discussionsupporting
confidence: 90%
“…These findings were in line with other observations showing that GA ameliorated clinical EAE scores, and that NK cells from these mice lysed both iDCs and mDCs [16]. These results indicated that one possible mechanism of GA inhibition may be to activate NK cells to lyse DCs (reviewed in [23]). Similarly, recent observations have shown that mitoxantrone, another drug used for treating MS, induces NK cell enrichment and maturation, which was associated with improved clinical response in secondary progressive MS [24].…”
Section: Discussionsupporting
confidence: 90%
“…Along these associations, there have been speculations as to how exactly NK cells mediate their effects, be it positive or negative. One suggested pathway was interactions between NK cells and dendritic cells [97,101] . The cognate and non-cognate interactions among NK cells and DCs have been previously described.…”
Section: Cd56mentioning
confidence: 99%
“…Further research divided these NK cells into even smaller subsets, recognized as NK22 secreting IL-22 and found in lymphoid tissues of the gastrointestinal tract [94] , or NK17/NK1 cells secreting IL-17 and IFN-γ when stimulated with IL-2 [95] . The role of NK cells in autoimmune diseases is being investigated, and is highly debated as both positive and negative associations have been observed [96][97][98][99] . In the EAE model, depletion of NK cells resulted in a severe relapsing EAE, and more pronounced CNS pathology [100][101][102][103] .…”
Section: Cd56mentioning
confidence: 99%
“…We focused on the perivascular space (PVS) of the brain because this is the vascularized area where autoreactive cells extravasate into the brain parenchyma. 4,5 Normal mice treated with vehicle showed normal PVS with no T cell infiltration or demyelination as determined by H & E staining, shown in Figure 6A. In contrast, EAE mice showed significant demyelinating areas presented as less myelin density, in addition to areas of loss of myelination in the white matter, as determined by Luxol fast staining ( Figure 6).…”
Section: Histopathological Evaluation Of the Cns Inflammation In Eae mentioning
confidence: 96%
“…It is believed that T cells are activated in the periphery, and then enter the CNS through at least two distinct sites including the subarachnoid space via the choroid plexus, or through the perivascular space at the blood-brain barrier. 4,5 On the other hand, B cells play an essential role in MS, both in humans and mouse models, 6 and are considered very important therapeutic targets for this disease. Cells of the B lymphocyte lineage are found to persist in the inflamed MS central nervous system and occupy multiple sub-compartments.…”
Section: Introductionmentioning
confidence: 99%